Renal tuberculosis in infancy - A K Dhua; N Borkar; V Ghosh; S K Aggarwal (Journal of Indian Association of Pediatric Surgeons, 2011)
We report a case of congenital renal tuberculosis in a 34-day-old child presenting as severe hematuria. Adequate antitubercular treatment may provide protection to fetus in subsequent pregnancies.